Electrophysiological studies of texture recognition mechanisms - Kharauzov, A. K.; Shelepin, Yu. E.; Pronin, S. V.; Sel’chenkova, T. V.; Noskov, Ya. A. (Neuroscience and behavioral physiology, 2008)
We report here our electrophysiological and psychophysiological studies of the mechanisms by which the visual system recognizes structured images with different levels of ordering. Visual stimuli consisted of textures, i.e., a set of matrixes consisting of Gabor grids. Matrixes differed in terms of the degree of ordering resulting from changes in the probability that grids with the same orientation would appear. The subject’s task was to identify the dominant orientation in the stimulus. The relationship between response accuracy, reaction time, and the main characteristics of evoked potentials on the one hand, and the number of identical grids in the matrix on the other was identified. The proportion of correct responses increased and the reaction time decreased as the degree of ordering of stimuli increased. Visual evoked potentials recorded in the occipital areas showed a relationship between the amplitudes of the N2, P2, and P3 waves, with latent periods of 180, 260, and 400 msec, respectively, and matrix parameters. The amplitudes of the P3 component and the positive component recorded in the frontal leads, with a latent period of 250 msec, increased gradually as the task became simpler. The amplitude of the N2 wave also increased with increases in the number of identically oriented elements in the matrix, though this relationship was S-shaped. The magnitude of the P2 component, conversely, was maximal in response to presentation of those matrixes which were most complex to recognize and gradually decreased as the content of identically oriented grids in the matrix increased. These relationships were compared with the statistical characteristics of the stimuli and assessed in terms of the view that the visual system contains two mechanisms, i.e., local and integral image descriptions.